Enzymes required for the biosynthesis of N-formylated sugars. (December 2016) - Holden, Hazel M; Thoden, James B; Gilbert, Michel
Graphical abstract: Highlights: The recent structural investigations on amino sugar N -formyltransferases are reviewed. Abstract : The N -formyltransferases, also known as transformylases, play key roles in de novo purine biosynthesis where they catalyze the transfer of formyl groups to primary amine acceptors. These enzymes require N 10 -formyltetrahydrofolate for activity. Due to their biological importance they have been extensively investigated for many years, and they are still serving as targets for antifolate drug design. Most of our understanding of the N -formyltransferases has been derived from these previous studies. It is now becoming increasingly apparent, however, that N -formylation also occurs on some amino sugars found on the O-antigens of pathogenic bacteria. This review focuses on recent developments in the biochemical and structural characterization of the sugar N -formyltransferases.